Development, performance evaluation, and clinical application of a Rapid SARS‐CoV‐2 IgM and IgG Test Kit based on automated fluorescence immunoassay. Issue 5 (1st March 2021) - Kang, Keren; Huang, Lingfang; Ouyang, Chaolin; Du, Jiaming; Yang, Bin; Chi, Yaqin; He, Shuyu; Ying, Le; Chen, Guoling; Wang, Jihua
Abstract: The ongoing coronavirus disease 2019 (COVID‐19) epidemic has made a huge impact on health, economies, and societies all over the world. Although reverse transcription‐polymerase chain reaction (RT‐PCR)‐based nucleic acid detection has been primarily used in the diagnosis of COVID‐19, it is time‐consuming with limited application scenarios and must be operated by qualified personnel. Antibody test, particularly point‐of‐care antibody testing, is a suitable complement to nucleic acid test as it provides rapid, portable, and cost‐effective detection of infections. In this study, a Rapid Antibody Test Kit was developed based on fluorescence immunochromatography for the sensitive, accurate, and automated detection of immunoglobulin M (IgM) and IgG antibodies against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) in human serum, plasma, and whole blood samples within 10 min. The sensitivity, specificity, precision, and stability of the test kit were of good performance. No cross‐activity and no interference was observed. In the multiple‐center parallel study, 223 samples from hospitalized patients were used to evaluate the clinical specificity of the test. Both SARS‐CoV‐2 IgM and IgG achieved a clinical specificity of 98.21%. The clinical sensitivities of SARS‐CoV‐2 IgM and IgG were 79.54% and 87.45%, respectively, among 733 reverse transcription‐polymerase chain reaction (RT‐PCR) confirmed SARS‐CoV‐2 samples. For the combined IgM and IgG assays, the sensitivity and specificity were 89.22% and 96.86%, respectively. Our results demonstrate that the combined use of IgM and IgG could serve as a more suitable alternative detection method for patients with COVID‐19, and the developed kit is of great public health significance for the prevention and control of the COVID‐19 pandemic. Highlights: We developed a rapid SARS‐CoV‐2 IgM and IgG test, which could be easy‐use and automatic for prevention and control of the COVID‐19 pandemic. The test showed good performance in evaluation of sensitivity, specificity, precision, and stability, and no cross‐activity and interference was observed. The combined use of IgM and IgG showed could be more suitable for COVID‐19 patients.